Reactive Power Impacts on LCL Filter Capacitor Lifetime in Grid-Connected Inverter - Dao Zhou; Huai Wang; Frede Blaabjerg (IEEE Open Journal of Power Electronics, 2020)
With the increasing penetration of renewable power, its reliability and cost-effective production are becoming more important. A filter is inserted between the grid-connected inverter and the power grid to reduce the PWM switching harmonics, which may become a fragile part seen from the power electronics converter perspective. As the grid-connected inverter is typically designed with additional reactive power capability, this paper tries to investigate the additional stresses of the filter capacitor introduced by the reactive power injection. According to an electro-thermal stress evaluation, the time-to-failure distribution of a single LCL filter capacitor is investigated in detail. Moreover, the increasing equivalent series resistance along with the operational period is taken into account. Aiming towards a system-level reliability analysis, a Weibull distribution based reliability of an individual capacitor can be linked to the reliability of a capacitor bank by using a reliability block diagram. A case study of a 2 MW wind power converter shows that the lifetime is significantly reduced from the individual capacitor to the capacitor bank. Besides, over-excited reactive power injection further reduces the lifetime of the LCL filter capacitors.